Improvement in metabolic effects by dietary intervention is dependent on the precise nature of the developmental programming challenge. (10th April 2015) - Bautista, C. J.; Guzmán, C.; Rodríguez-González, G. L.; Zambrano, E.
Abstract : Predisposition to offspring metabolic dysfunction due to poor maternal nutrition differs with the developmental stage at exposure. Post-weaning nutrition also influences offspring phenotype in either adverse or beneficial ways. We studied a well-established rat maternal protein-restriction model to determine whether post-weaning dietary intervention improves adverse outcomes produced by a deficient maternal nutritional environment in pregnancy. Pregnant rats were fed a controlled diet (C, 20% casein) during pregnancy and lactation (CC) or were fed a restricted diet (R, 10% casein isocaloric diet) during pregnancy and C diet during lactation (RC). After weaning, the offspring were fed the C diet. At postnatal day (PND) 70 (young adulthood), female offspring either continued with the C diet (CCC and RCC) or were fed commercial Chow Purina 5001 (I) to further divide the animals into dietary intervention groups CCI and RCI. Another group of mothers and offspring were fed I throughout (III). Offspring food intake was averaged between PND 95–110 and 235–250 and carcass and liver compositions were measured at PND 25 and 250. Leptin (PND 110 and 250) and serum glucose, triglycerides and cholesterol (PND 250) levels were measured. Statistical analysis was carried out using ANOVA. At PND 25, body and liver weights were similar between groups; however, CCC and RCC carcass protein:fat ratios were lower compared with III diet. At PND 110 and 250, offspring CCC and RCC had higher body weight, food intake and serum leptin compared with CCI and RCI. CCI had lower carcass fat and increased protein compared with CCC and improved fasting glucose and triglycerides. Adult dietary intervention partially overcomes adverse effects of programming. Further studies are needed to determine the mechanisms involved.